An evaluation of the effectiveness of diploma-level training in cognitive behaviour therapy. - McManus, F; Westbrook, D; Vazquez-Montes, M; Fennell, M; Kennerley, H (2010)
BACKGROUND: As part of the UK government's initiative to Increase Access to Psychological Therapies (see http://www.iapt.nhs.uk/for full details of the IAPT programme) there has been an expansion in the provision of post-graduate Diploma training in cognitive behaviour therapy (CBT). Previous evaluations of such training programmes have yielded mixed results but have been limited by small sample sizes and/or limited assessment measures. AIMS: To evaluate the impact of a long-standing Diploma in CBT training programme on a variety of measures of CBT competence. METHOD: Trainees' levels of CBT skill are compared at the beginning and end of CBT training. The effect of therapist factors such as age, professional background and gender on the development of CBT competence is also examined. RESULTS: Results show that trainees demonstrate higher levels of CBT skills after completing the training than they did before, with the majority achieving pre-determined criteria for competence. Trainees' gender was not related to their performance but trainees' age showed a negative association with CBT skill (older trainees performed worse). Trainees' professional background also had an impact on their level of CBT competence, with trainees who were clinical psychologists demonstrating the highest levels of competence across a range of measures. CONCLUSIONS: CBT Diploma training leads to increases in the level of trainees' CBT competence, with the majority achieving the levels demonstrated in research trials by the end of training. Thus, this training is likely to lead to improved outcomes for patients. Further research is needed to determine the most efficient ways of enhancing CBT skills.